Portuguese Football Coaches’ Role in Facilitating Positive Development Within High Performance Contexts: Is Positive Development Relevant? - Santos, Fernando (2018)
Over the last decades positive development (PD) has served as a framework for several investigations within the sport science community. In fact, multiple researchers have analyzed youth coaches’ role in PD. However, there is recent interest in exploring high performance coaching due to the complexity of the coaching practice, the different developmental needs presented by players, and the relevance of PD within this particular environment. The purpose of this study was to understand the perspectives of Portuguese football coaches about the importance of PD in high performance coaching. The participants in the study were ten male Portuguese football coaches who trained athletes between the ages of 16 and 39 years of age. Findings showed that coaches viewed winning and on field performance as top priorities in their coaching philosophy, but recognized the importance of PD. Coaches also envisioned the determinant role youth coaches have in this domain. Coaches conceptualized PD as an overarching framework that could be used across the developmental spectrum to convey a range of PD outcomes in high performance contexts such as teamwork, respect for others and transfer to other life domains. Moving forward, coach education courses should help coaches develop strategies to foster PD.